COVER SONG ANALYSIS OF SELECTED ONE DIRECTION PERFORMANCES IN THE X FACTOR UK SEASON 7 - Chory Afri Andari (CrossOver, 2023)
This research's purpose is to find out the type of cover songs sung by One Direction and the employment of ethnography of communication aspects shown from their performances. Two theories have been used to analyze this research's data: cover songs theory by Mosser (2008) and the ethnography of communication theory by Hymes (1972). The descriptive qualitative method is applied because it is aimed at comprehending a specific group case. The researcher herself and some helping tools such as; word processor, referential sources, and YouTube platform are this research's instruments. The data are taken from One Direction's selected performances in The X Factor UK Season 7. Data was obtained by watching selected One Direction performances, and interpretation was made by classifying and analyzing selected performances using the underlying theories. The results showed that One Direction mostly used the reduplication cover while singing the songs they had picked together. Besides, two other types of cover song, namely the interpretive cover, are also found, and it consists of major and minor interpretive cover. Six selected performances of One Direction in The X Factor UK Season 7 took place around October until December 2010 on The X Factor UK's stage, involving some performers and judges, and having both some patterns and specific behaviors shown from the singing turn by the members and the judges' way of commenting. In addition, the songs One Direction members have performed have several different tones that they successfully sing. The goals-oriented genre makes One Direction the 3rd winner of The X Factor UK Season 7.